Role of protein kinase C in cAMP-dependent exocytosis in parotid acinar cells - Hiroshi Sugiya; Keitaro Satoh (Elsevier, 2009)
It is well known that β-adrenergic receptor activation in parotid acinar cells results in increased intracellular cAMP levels, and consequently induces exocytotic amylase release. However, protein kinase C (PKC) has also been considered to contribute to amylase release. In this paper, we review the role of PKC in cAMP signaling and amylase release. PKCδ, a so-called 'novel PKC', has been shown to be activated by β-adrenergic receptor stimulation. Myristoylated alanine-rich C kinase substrate (MARCKS), a major cellular substrate for PKC, is detected in parotid acinar cells, and MARCKS phosphorylation and translocation from the membrane to the cytosol are induced by β-adrenergic receptor stimulation. cAMP-dependent protein kinase (PKA) inhibitor inhibits β-agonist-induced PKC activation and MARCKS phosphorylation. The β-agonist-induced amylase release is inhibited by inhibitors of PKCδ or by a MARCKS-related peptide. These findings suggest that MARCKS phosphorylation via PKCδ activation, which is downstream of PKA activation, is involved in the cAMP-dependent amylase release in parotid acinar cells.